Advancing Zebrafish (Danio rerio) Welfare Using Immersion Analgesics - Cláudia A. Rocha; Luís M. Félix; Sandra M. Monteiro; Carlos Venâncio (Veterinary Sciences, 2025)
Growing evidence of pain perception in fish has raised concerns about their welfare in different contexts, including research and aquaculture, where potentially painful procedures are standard. Despite ongoing efforts to advance fish analgesia, the field remains underdeveloped, particularly regarding less invasive methods that could improve welfare, such as immersion-based analgesia. As one of the most widely used models in research, zebrafish (Danio rerio) are often at the front of these concerns. This review aimed to consolidate the current knowledge on immersion analgesics by analyzing the behavioral responses of zebrafish exposed to noxious stimuli. Some promising immersion analgesics were identified; however, further research is needed to assess their effects on additional parameters and investigate potential adverse effects. These findings underscore the importance of selecting appropriate analgesics, as their effectiveness may vary depending on the duration and severity of the stimulus. Moreover, this review highlights the critical role of consistent water quality monitoring and detailed parameter reporting, as these factors may influence analgesic efficacy and compromise fish welfare. As research advances, applying these insights beyond zebrafish to other fish species will be crucial for promoting higher welfare standards.